المركز القانوني لللجنة الإدارية متساوية الأعضاء في التشريع الجزائري - ترايعية أحمد; روابحية زكرياء (My University, 2022)
summary: Administrative committees with equal members are considered the most important guarantee for the public employee through their efforts to reconcile the public and private interests on the one hand and to try to limit the broad powers and the abuse of public administrations in the face of ......... or at least control them in accordance with the regulations. Thus, they are advisory bodies that are established at the level of various public institutions and administrations and are composed of an equal number of representatives of the administration and employees. Consultation takes place in many areas related to the conduct of the professional life of employees, and their opinions range from mere advice and commitment according to the situation, as it enables employees to participate in the conduct of their career path Through their elected representatives, a judicial body shall be established with jurisdiction to consider disciplinary sanctions of the third and fourth degree. ..................... ملخص المذكرة : تعد اللجان الإدارية متساوية الأعضاء أهم ضمانة بالنسبة للموظف العام من خلال سعيها للتوفيق بين المصلحتين العامة والخاصة من جهة ومحاولة الحد من السلطات الواسعة ومن تعسف الإدارات العمومية في مواجهة الموظفين أو على الأقل ضبطها بما يتوافق والتنظيمات. وهي بذلك هيئات استشارية تنشأ على مستوى مختلف المؤسسات والإدارات العمومية، وتتشكل من عدد متساوي من ممثلي الإدارة والموظفين وتتم الاستشارة في العديد من المجالات التي تخص تسيير الحياة المهنية للموظفين وتتراوح أرائيها بين مجرد الاستشارة والالتزام على حسب الحالة كما أنها يمكن للموظفين من المشاركة في تسيير مسارهم المهني عن طريق ممثليهم المنتخبين، وتعد هيئة به قضائية تختص بالنظر في العقوبات التأديبية من الدرجة الثالثة والرابعة. ........................... résumé : Les comités administratifs composés de membres égaux sont considérés comme la garantie la plus importante pour le fonctionnaire par leurs efforts pour concilier les intérêts publics et privés, d’une part, et pour tenter de limiter les pouvoirs étendus et les abus des administrations publiques ... ou du moins les contrôler conformément aux règlements. Il s’agit donc d’organismes consultatifs établis au niveau de diverses institutions et administrations publiques et composés d’un nombre égal de représentants de l’administration et des employés. La consultation a lieu dans de nombreux domaines liés à la conduite de la vie professionnelle des employés, et leurs opinions vont du simple conseil et engagement selon la situation, Dans la mesure où il permet aux salariés de participer à la conduite de leur carrière Par l’intermédiaire de leurs représentants élus, un organe judiciaire est constitué avec compétence pour examiner les sanctions disciplinaires du troisième et du quatrième degré.